PKM Development of Craftsmen Business Group Keben Banjar Tanggahan Peken Sulahan Village Susut District Bangli Regency - Wirata, Gede; Handayani, Made Mulia (Universitas Pendidikan Ganesha, 2022)
The keben craft business is a business that has the opportunity to develop, in the life of the Balinese people, keben is a means of prayer and various other traditional activities, so that the keben craft business is a promising business opportunity. Partners in the internal PKM activities of group 10 at Ngurah Rai University are the keben craftsmen group, namely the Keben Asti Craftsmen Group located in Banjar Tanggahan Peken, Sulahan Village, Susut District, Bangli Regency. The purpose of implementing this PKM is to develop a group of Asti keben crafts in BanjarTanggahan Peken. After conducting observations and interviews with the head of the Asti keben craftsman group in Banjar Tanggahan Peken, the following problems were found: 1) The Asti keben craftsman business group has not been able to manage the tasks of each group member. 2) The production factors still use traditional and manual methods such as making bamboo cuttings, they still use knives so that it slows down the production process, 3), partners do not know and understand how to make simple bookkeeping, 4) Promotion is still limited and only by word of mouth (WOM). ). 5) do not have a business WEB and business nameplate. The PKM activities provided are 1) Providing group management training, 2) providing assistance in the form of a bamboo shaving machine to simplify and speed up the production process, 4). Problems in the field of management, the solution offered is to provide simple bookkeeping training to be able to record costs and find out earned income. 5) Problems in promoting the product solutions offered, promotional training using social media, and creating a business WEB. The outputs produced are articles in national journals, articles in printed mass media, videos of the implementation of activities, 20% increase in production capacity and quality, capability business management both in the field of promotion and financial management and able to make simple bookkeepingÂ